Analysis of the Use of Economic Value Added (EVA) to Measure Financial Performance at PT. Astra Agro Lestari Tbk Listed on the Indonesia Stock Exchange (BEI) - Febrianti Pratiwi; Muh. Alam Nasyrah Hanafi; Abdul Hafid Burhami (Yayasan Adra Karima Hubbi, 2024)
This research aims to determine the use of Economic Value Added (EVA) to measure financial performance at PT. Astra Agro Lestari Tbk. period 2019 to 2023. This research uses quantitative analysis methods using secondary data sources with documentation data collection techniques, data analysis techniques using EVA (Economic Value Added) which consists of NOPAT and capital charges. The research results show that in 2019 the financial performance of PT. Astra Agro Lestari Tbk is said to be not good, because the EVA value produced is negative (EVA<0). In 2020-2023 the financial performance of PT. Astra Agro Lestari Tbk. is said to be good because the resulting EVA value is positive (EVA>0).